Physician education can minimize inappropriate steroid use in patients with inflammatory bowel disease: the ACTION study - Yehyun Park; Chang Hwan Choi; Hyun Soo Kim; Hee Seok Moon; Do Hyun Kim; Jin Ju Kim; Dennis Teng; Dong Il Park (Intestinal Research, 2022)
Background/Aims Epidemiological data on steroid use in South Korean patients with inflammatory bowel disease (IBD) are limited. We documented the steroid use patterns in these patients, and whether physician education on appropriate steroid use affected these patterns. Methods ACTION was an observational cohort study conducted in adults (≥19 years) with IBD. A retrospective chart review was performed at baseline (cohort 1) and 1 year after physician training (cohort 2). Eligible cases with excessive or inappropriate steroid use were identified, along with any associated risk factors. Results Data were collected during May 2018-July 2019 from patients with Crohn’s disease (CD) and ulcerative colitis (UC) in cohort 1 (n=1,685) and cohort 2 (n=1,649). At baseline, 155 patients (9.2%) had received steroids within the previous 12 months, 46 (29.7%) of whom had used steroids excessively, 16 (34.8%) of these having inappropriately used excessive steroids. Although steroid exposure was similar in cohort 1 (9.2%) and cohort 2 (9.7%), the latter comprised fewer excessive steroid users (20.0% vs. 29.7%). Severe disease was associated with excessive steroid use in cases with UC, but not with CD. Conclusions Although, overall steroid use was relatively low in South Korean patients with IBD, one-third of steroid users used them excessively, and one-third among these used excessive steroids inappropriately. High disease activity was the main risk factor for excessive steroid use which may potentially be reduced by physician education, especially in cases with UC. Active screening to minimize excessive and inappropriate steroid use through physician education should be considered.